SOSIALISASI PEMANFAATAN BAHAN ALAM SEBAGAI ANTIACNE DAN KEAMANAN PENGGUNAAN ACNE PATCH PADA REMAJA - Wahyu Purwanjani; Renno Ramadhani Ika Baruna; Muhammad Nur Prasetyo; Supriyanto (LPPM AN Nuur, 2026)
Background: Acne vulgaris is one of the most common skin problems experienced by adolescents, resulting from hormonal changes, increased sebum production, Cutibacterium acnes colonization, and pilosebaceous follicle inflammation. Limited understanding among adolescents regarding the causes of acne, appropriate treatment, and the widespread use of instant products such as acne patches without adequate knowledge of proper application and safety limits underline the importance of early skin health education. Purpose: This community service activity aimed to improve adolescents' knowledge and awareness regarding the use of natural ingredients as antiacne agents and the safe use of acne patches. Method: The activity was carried out through interactive counseling, demonstration, and distribution of educational media to adolescent participants at [name of partner school/location]. The implementation method consisted of preparation (needs assessment and material development), implementation (lectures, discussion, and demonstration of correct acne patch application), and evaluation using pretest and posttest questionnaires. Results: The results showed an increase in participants' knowledge scores after the socialization, along with high enthusiasm reflected in an active question-and-answer session. Participants also demonstrated a better understanding of natural ingredients such as tea tree oil, aloe vera, green tea extract, and Centella asiatica as alternative acne treatments, as well as an awareness of the risk of irritation from improper acne patch use, particularly on open wounds or actively infected skin. Conclusion: This activity is expected to serve as a model for sustainable education to improve skin health literacy among adolescents. Keyword: acne vulgaris; natural ingredients; acne patch; health education; adolescents